ON THE IMPORTANCE AND NEED OF FLEXIBILITY AND STRENGTH REFINEMENT AS AN ELEMENT OF DANCERS’ TRAINING - Ina Vladova; Yiğit Ünlü (Journal of Applied Sports Sciences)
Contemporary professional dance art is close, to a great extent, to sport of excellence. The requirements to performers are constantly increasing and hence the need of properly organised specialised training, including a system of drills, stretching and dance exercise for developing their motor skills. The aim of this empirical study is to establish the need of including a specialised methodology for the development of the motor skills in the dance practice in the Republic of Turkey – strength and flexibility for the dancers of Turkish folk dances. The tasks are: to study the dance practice in the Republic of Turkey and to explore the views of the future dance pedagogues on the implementation of a program in dance training for the development of motor skills. The survey was conducted among dance students of Turkish folk dances with the help of a specially designed questionnaire. Our sustained observations and the analysis of the existing literature show lack of exhaustive research in the field of the dance theory and practice in the Republic of Turkey. There is insufficient data on the existence of a uniform methodology for working in the dance groups for the development of flexibility and strength with the use of specially elaborated programs, including dance exercises. The results of the conducted survey confirm the absence of a unified and purposeful work in this area. At present, in teaching dance, there is not enough emphasis put on the purposeful development of dancers’ motor skills. Given the increasing requirements dancers face, we consider it unreasonable that the scientific achievements not be widely introduced in the pedagogic practice in Turkey. Such discrepancy between theory and practice may have serious consequences – an increased risk of injuries and lasting disabilities, shorter career as a dancer and a debased professional satisfaction.